GERMLINE PATHOGENIC VARIANTS IN PATIENTS WITH PANCREATIC DUCTAL ADENOCARCINOMA AND EXTRA-PANCREATIC MALIGNANCIES: A NATIONWIDE DATABASE ANALYSIS - Valentyna Kryklyva; Michael J. Pflüger; Hicham Ouchene; Hanneke Volleberg-Gorissen; Arjen R. Mensenkamp; Marianne A. Jonker; Carlijn van de Water; Irıs D. Nagtegaal; Marjolijn J. L. Ligtenberg; Lodewijk A.A. Brosens (2025)
Pancreatic ductal adenocarcinoma (PDAC) is a lethal disease. About 10% of affected individuals have an inherited component. Deleterious germline variants increase the lifetime risk for PDAC and are often associated with an elevated risk for extra-pancreatic malignancies. In this study, we aim to determine the prevalence and impact of germline pathogenic variants (gPVs) in patients with PDAC and extra-pancreatic malignancies. Using tissue samples and longitudinal data from a nationwide pathology database, we identified patients with PDAC and a set of seven extra-pancreatic malignancies to investigate the presence of gPVs in 25 cancer susceptibility genes with targeted next-generation sequencing. Of 473 PDAC patients with at least one extra-pancreatic malignancy, 75 (16%) had gPVs. These were predominantly in ATM (n=22), CDKN2A (n=14), BRCA2 (n=10), or CHEK2 (n=10) genes. The combination of PDAC and ovarian carcinoma carried the highest prevalence of gPVs (4 of 10; 40%), followed by PDAC and melanoma (15 of 53; 28%), and PDAC and gastric cancer (2 of 9; 22%). PDAC patients with certain extra-pancreatic malignancies carry a higher burden of gPVs than unselected PDAC cohorts. This is a group that very likely benefits from genetic testing since germline status can have important diagnostic and therapeutic implications for affected individuals and their family members.